Fibrinolytic Activity of the Arterial Wall - Onoyama, K; Tanaka, K (Thrombosis and Haemostasis, 1969)
The tissue fibrinolysis was studied in 550 specimens of 7 kinds of arteries from 80 fresh cadavers, using Astrup’s biochemical method and Todd’s histochemical method with human fibrinogen.In the microscopically normal aortic wall, almost all specimens had the fibrinolytic activity which was the strongest in the adventitia and the weakest in the media.The fibrinolytic activity seemed to be localized in the endothelium.The stronger activity lay in the adventitia of the aorta and the pulmonary artery and all layers of the cerebral artery.The activity of the intima and media of the macroscopically normal areas seemed to be stronger in the internal carotid artery than in the common carotid artery.Mean fibrinolytic activity of the macroscopically normal areas seemed to decrease with age in the intima and the media of the thoracic aorta and seemed to be low in the cases with a high atherosclerotic index.The fibrinolytic activities of all three layers of the fibrous thickened aorta seemed to decrease, and those of the media and the adventitia of the atheromatous plaque to increase.The fibrinolytic activity of the arterial wall might play some role in the progress of atherosclerosis.